Empfehlungen der aktualisierten Leitlinie LONTS - Häuser, Winfried; Schiltenwolf, Marcus (Der Schmerz, 2015)
BackgroundThe regular update of the German S3 guidelines on long-term opioid therapy for chronic noncancer pain (CNCP), the“LONTS” (AWMF registration number 145/003), began in November 2013.MethodsThe guidelines were developed by 26 scientific societies and two patient self-help organisations under the coordination of the Deutsche Schmerzgesellschaft (German Pain Society). A systematic literature search in the Cochrane Central Register of Controlled Trials (CENTRAL), Medline and Scopus databases (up until October 2013) was performed. Levels of evidence were assigned according to the classification system of the Oxford Centre for Evidence-Based Medicine. The strength of the recommendations was established by multistep formal procedures, in order to reach a consensus according to German Association of the Medical Scientific Societies (“Arbeitsgemeinschaft der Wissenschaftlich Medizinischen Fachgesellschaften”, AWMF) regulations. The guidelines were reviewed by the Drug Commission of the German Medical Association, the Austrian Pain Society and the Swiss Association for the Study of Pain.ResultsOpioids are one drug-based treatment option for short- (4-12 weeks), intermediate- (13-25 weeks) and long-term (≥ 26 weeks) therapy of chronic osteoarthritis, diabetic polyneuropathy, postherpetic neuralgia and low back pain. Contraindications are primary headaches, as well as functional somatic syndromes and mental disorders with the (cardinal) symptom pain. For all other clinical presentations, a short- and long-term therapy with opioid-containing analgesics should be evaluated on an individual basis. Long-term therapy with opioid-containing analgesics is associated with relevant risks (sexual disorders, increased mortality).ConclusionResponsible application of opioid-containing analgesics requires consideration of possible indications and contraindications, as well as regular assessment of efficacy and adverse effects. Neither an uncritical increase in opioid application, nor the global rejection of opioid-containing analgesics is justified in patients with CNCP.